Tail of the whale appearance: A pathognomonic feature of scleroderma - Manisha Lakhanpal Sharma; Gayatri Mehrotra; Komal Sharma; Sricha Suman (Wolters Kluwer Medknow Publications, 2020)
Scleroderma is a rare connective tissue disorder of unknown etiology characterized by fibrosis of skin, blood vessels, and internal organs. Orofacial changes include mask-like facies, microstomia, xerostomia, and stiffness of tongue with reduced mouth opening. The radiographic features are very characteristic which includes symmetrical widening of periodontal ligament space and bone resorption. We, hereby present a case of 55-year-old female patient of Scleroderma presenting with a typical radiographic feature of "Tail of the whale" appearance due to resorption of the ramus of mandible.